The Impact of Artificial Intelligence on Drug Discovery; A Comprehensive Review - Kazi, Anis J.; Gurav, Mohini A.; Patil, Sneha R.; Ritthe, Punam V.; Rudrurkar , Muktai N.; Dharashive, Vishweshwar M. Dharashive; Shafi, Dr. Sameer (Asian Journal of Pharmaceutical Research and Development, 2024)
Artificial Intelligence (AI) is a technology that utilizes knowledge and learning to solve complicated problems. Recent advancements in computational power and AI technology have significantly increased its potential to revolutionize the drug development process. The pharmaceutical industry is among the primary beneficiaries of AI's recent applications in various sectors of society. In this review, we will discuss the primary causes of attrition rates in new drug approvals, explore how AI can improve the efficiency of the drug development process, and examine the collaboration between pharmaceutical industry leaders and AI-powered drug discovery firms.